Distribution and Determinants of Metabolic Syndrome in Non-Obese Hypothyroid Patients - CD, Preethi; Anuradha, N; Prabhu, Viknesh; Preethi, Anis; Ashwathy, Ashwathy (Journal of Neonatal Surgery, 2025)
A number of metabolic and cardiovascular parameters may be profoundly impacted by hypothyroidism, a prevalent endocrine condition. The aim of this study was to determine the prevalence and risk factors of metabolic syndrome in hypothyroidism patients who are not overweight. This research lasted two years in a private medical college, Tamil Nadu between 2022 and 2024. Among 138 hypothyroidism patients the most significant group consisted of individuals from age 41 to 50 (28%). Females constituted majority (57%) of the study population. Hypertension was present in 32% of the patients, while diabetes mellitus was found in 29%. Elevated waist circumference was observed in 38% of the patients. High blood pressure was recorded in 22% of the patients. Regarding HbA1c levels, 55% had levels > 6.5%, indicating poor glycaemic control. While 38% of patients had total cholesterol levels over 200 mg/dL, 55% had triglyceride levels above 150 mg/dL. It was shown that 51% of the patients had low HDL levels (< 40 mg/dL) and 85% had high LDL levels (> 100 mg/dL), respectively. Patients with hypothyroidism are more likely to have metabolic and cardiovascular risk factors, according to this research. The need of doing thorough assessments and managing cardiovascular risk factors in this group is highlighted by these results. Regular monitoring and early intervention can help mitigate long-term risks associated with hypothyroidism.